2017
DOI: 10.1186/s12934-017-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of an antibiotic marker-free platform for heterologous protein production in Streptomyces

Abstract: BackgroundThe industrial use of enzymes produced by microorganisms is continuously growing due to the need for sustainable solutions. Nevertheless, many of the plasmids used for recombinant production of proteins in bacteria are based on the use of antibiotic resistance genes as selection markers. The safety concerns and legal requirements surrounding the increased use of antibiotic resistance genes have made the development of new antibiotic-free approaches essential.ResultsIn this work, a system completely f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…by laboratory methods [41,42]. It has been suggested that TAs YoeB/YefM from S. lividans is a powerful tool for producing other proteins of interest in Streptomyces without the use of antibiotics in the production step [43,44]. Thus, TAs are expected to be a valuable tool for the mass production of metabolites in Streptomyces .…”
Section: Discussionmentioning
confidence: 99%
“…by laboratory methods [41,42]. It has been suggested that TAs YoeB/YefM from S. lividans is a powerful tool for producing other proteins of interest in Streptomyces without the use of antibiotics in the production step [43,44]. Thus, TAs are expected to be a valuable tool for the mass production of metabolites in Streptomyces .…”
Section: Discussionmentioning
confidence: 99%
“…But then again, the usage of antibiotics in industrial production of enzymes should be maximally minimized, not just for reduction in production costs, but also because of the emergence of antibiotic-resistant strains and complexed legal requirements. The expression platform without antibiotic resistance genes was developed and tested for production of two hydrolytic enzymes in S. lividans (Sevillano et al 2017 ). In this system, the toxin gene was integrated into the S. lividans genome, while the expression plasmid carried the antitoxin gene, which served to inactivate the toxin.…”
Section: Industrially Relevant Enzymes Produced In Streptom...mentioning
confidence: 99%
“…The more recent pIJ86 carries apramycin resistance marker ( aprR ) and it is a conjugative vector used for the strong constitutive expression of proteins under erythromycin promoter ( ermE ∗ promoter) from Saccharopolyspora erythraea . Recent works ( Sevillano et al, 2013 , 2017 ) described new replicative high copy number ‘marker-free’ systems, which allowed the production of high levels of proteins without using antibiotics as selection markers. One example is based on the presence of a toxin gene localized in the genome and of an anti-toxin gene located on the expression plasmid of the yefM/yoeBsl operon from S. lividans ( Sevillano et al, 2013 ).…”
Section: Which Is the Best Promoter/vector/host System For Recombinanmentioning
confidence: 99%